Data from: Signatures of selection acting on the innate immunity gene Toll-like receptor 2 (TLR2) during the evolutionary history of rodents - Tschirren, Barbara; Råberg, Lars; Westerdahl, Helena (Zenodo, 2011)
Patterns of selection acting on immune defence genes have recently been the focus of considerable interest. Yet, when it comes to vertebrates, studies have mainly focused on the acquired branch of the immune system. Consequently, the direction and strength of selection acting on genes of the vertebrate innate immune defence remain poorly understood. Here, we present a molecular analysis of selection on an important receptor of the innate immune system of vertebrates, the Toll-like receptor 2 (TLR2), across 17 rodent species. Although purifying selection was the prevalent evolutionary force acting on most parts of the rodent TLR2, we found that codons in close proximity to pathogen-binding and TLR2–TLR1 heterodimerization sites have been subject to positive selection. This indicates that parasite-mediated selection is not restricted to acquired immune system genes like the major histocompatibility complex, but also affects innate defence genes. To obtain a comprehensive understanding of evolutionary processes in host–parasite systems, both innate and acquired immunity thus need to be considered. Tschirren_TLR2sequences DNA sequences of the entire coding region of the Toll-like receptor 2 (TLR2) gene of Myodes glareolus, Myodes rutilus, Myodes smithii, Myodes andersoni, Myodes rufocanus, Myodes rex, Chionomys nivalis, Microtus agrestis, Microtus arvalis, Microtus oeconomus, Arvicola amphibius, Apodemus alpicola, Apodemus flavicollis, Apodemus sylvaticus, Micromys minutus, Mus musculus, Rattus norvegicus